Obesity and other Modifiable Cardiometabolic Risk Factors in Adolescents in Lagos, Nigeria - Salisu-Olatunji, S. O.; Odugbemi, Babatunde; Adejumo, O. A.; Mohammed, A. S.; Alakija, W (The Nigerian Health Journal, 2024)
Background: The true burden of non-communicable diseases and their risk factors among adolescents in developing countries is unknown. The objective was to assess the prevalence of obesity and other modifiable cardio-metabolic risk factors among adolescents in Lagos State, Nigeria. Method: A cross-sectional study design was used. Five hundred and six in-school adolescents were recruited through a multistage sampling technique. Data was collected using a questionnaire adapted from the WHO STEPS chronic disease surveillance tool. Anthropometric measurements were also taken. Respondents were classified as having either low or high metabolic risk based on computed risk scores. Logistic regression was used to determine the predictors of high metabolic risk. The level of significance was set at p<0.05. Ethical approval was obtained from the Health Research and Ethics Committee of the Lagos State University Teaching Hospital. Result: The overall prevalence of overweight/obesity was 7.7%. Ten percent of adolescents had poor physical activity levels, unhealthy dietary practices such as frequent intake of sugary snacks (20%), inadequate consumption of fruits (98%) and vegetables (99%,) and elevated blood pressure readings (5%). Five percent of respondents had a high total metabolic risk score. The predictors of high metabolic risk were BMI (OR: 18.72, 95%CI: 7.1-47.3), alcohol consumption (OR: 6.2, 95%CI: 1.9-20.8) and soft drink consumption (OR: 2.9, 95%CI: 0.8-3.4). Conclusion: Adolescents had modifiable risk factors for chronic diseases. Healthy food and physical activities should be available and made compulsory in schools to encourage health-promoting behaviours that will potentially help in the prevention of chronic cardio-metabolic conditions.